Role of chemotaxis in the association of motile bacteria with intestinal mucosa: fitness and virulence of nonchemotactic Vibrio cholerae mutants in infant mice - Rolf Freter; Patrícia C. M. O’Brien (1981)
Contrary to earlier findings with all other in vivo and in vitro models of cholera studied, nonchemotactic vibrio mutants showed a relatively greater fitness in 5-day-old infant mice as compared with chemotactic parent or chemotactic revertant strains. This trend was manifest in the relatively greater number of nonchemotactic mutants recovered from the upper small intestine at 4 and 18 h after intragastric infection. The same trend was also revealed in the significantly greater virulence (in terms of time to death) of nonchemotactic mutants as compared with the chemotactic parent or revertant strains. Histological studies in infant mice of the penetration of chemotactic and nonchemotactic vibrios into the mucus gel of the small intestine yielded the same findings as in all other models studied, i.e., significantly greater penetration by chemotactic vibrios. There was no correlation between the relative fitness of nonchemotactic vibrios in the small intestine of infant mice and the rate of recovery of viable nonchemotactic vibrios from that site. In contrast, excellent correlation was found between the relative fitness of nonchemotactic vibrios and a decrease in the recovery of viable cells of the chemotactic strain from the small intestine. This indicates that the relatively greater fitness of the nonchemotactic vibrios in infant mice was only apparent and that the observed phenomenon was actually due to an antibacterial mechanism which prevented the accumulation of the chemotactic strains in the small intestine rather than to any stimulating effect on the nonchemotactic mutant itself. To study the in vivo fate of the inoculum in infant mice, vibrios were labeled with either 32P, 35S, or [3H]thymidine. Specific activity determinations of the 32P label were compatible with the assumption of an accelerated rate of death of the chemotactic parent strain in the small intestine. Results with the other isotopes, however, were significantly different. Indeed, the amount of radioactivity retained in the small intestine after feeding labeled bacteria correlated more closely with the isotope used than with the strain of vibrio under study. Consequently, considerable doubt must be cast on the general validity of this not uncommon technique for determining the in vivo location and the death or survival of radioactively labeled bacteria.